Socioeconomic inequalities in avoidable mortality in Italy: results from a nationwide longitudinal cohort - Alessio Petrelli; Martina Ventura; Anteo Di Napoli; Marilena Pappagallo; Silvia Simeoni; Luisa Frova (BMC, 2024)
Abstract Background Disparities in avoidable mortality have never been evaluated in Italy at the national level. The present study aimed to assess the association between socioeconomic status and avoidable mortality. Methods The nationwide closed cohort of the 2011 Census of Population and Housing was followed up for 2012-2019 mortality. Outcomes of preventable and of treatable mortality were separately evaluated among people aged 30-74. Education level (elementary school or less, middle school, high school diploma, university degree or more) and residence macro area (North-West, North-East, Center, South-Islands) were the exposures, for which adjusted mortality rate ratios (MRRs) were calculated through multivariate quasi-Poisson regression models, adjusted for age at death. Relative index of inequalities was estimated for preventable, treatable, and non-avoidable mortality and for some specific causes. Results The cohort consisted of 35,708,459 residents (48.8% men, 17.5% aged 65-74), 34% with a high school diploma, 33.5% living in the South-Islands; 1,127,760 deaths were observed, of which 65.2% for avoidable causes (40.4% preventable and 24.9% treatable). Inverse trends between education level and mortality were observed for all causes; comparing the least with the most educated groups, a strong association was observed for preventable (males MRR = 2.39; females MRR = 1.65) and for treatable causes of death (males MRR = 1.93; females MRR = 1.45). The greatest inequalities were observed for HIV/AIDS and alcohol-related diseases (both sexes), drug-related diseases and tuberculosis (males), and diabetes mellitus, cardiovascular diseases, and renal failure (females). Excess risk of preventable and of treatable mortality were observed for the South-Islands. Conclusions Socioeconomic inequalities in mortality persist in Italy, with an extremely varied response to policies at the regional level, representing a possible missed gain in health and suggesting a reassessment of priorities and definition of health targets.